The Analysis of Factors that Influence the Level of Need on the Implementation of Occupational Health and Safety Management System (OSHMS) in the Kediri District Office of Health Office, 2020 - Yulita Amaliyasari; Yuly Periostiawati (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
The Occupational Safety and Health Management System (OSHMS) is part of the overall management system needed in order to control risks related to work activities in order to achieve a safe, comfortable and productive workplace. Kediri District Health Office has not implemented OSHMS. This study aims to analyze the factors that influence the level of need for the implementation of OSHMS in the Kediri District Health Office. This type of research uses quantitative research with cross sectional design. The employee population is 133 people, the sample size is 100 people, the statistical test used is ordinal regression. The results showed that there was one category of the comfort level variable of the work environment and a history of occupational diseases where p <0.05, while all categories of work culture variables (occupational safety and health behavior/OSH) and the level of satisfaction of infrastructure where p> 0.05 . So it can be concluded that there is an influence on one of the categories, namely the comfort level of the work environment in a good category with an odds ratio of 0.499 and a history of illness due to work in the moderate category with an odd ratio of 0.175 to the level of need for OSHMS implementation, and there is no influence on all categories of work culture (OSH behavior) and the level of satisfaction of infrastructure on the level of need implementation of OSHMS. Judging from the large value of the odds ratio, the comfort level of the work environment and the history of occupational diseases, the comfort level variable of the work environment has a greater odds ratio value than the history of occupational diseases, this means that the variable that most influences the level of need for application of OSHMS is the comfort level work environment.